2020
DOI: 10.1042/bcj20200506
|View full text |Cite
|
Sign up to set email alerts
|

Functions and regulation of the serine/threonine protein kinase CK1 family: moving beyond promiscuity

Abstract: Regarded as constitutively active enzymes, known to participate in many, diverse biological processes, the intracellular regulation bestowed on the CK1 family of serine/threonine protein kinases is critically important, yet poorly understood. Here, we provide an overview of the known CK1-dependent cellular functions and review the emerging roles of CK1-regulating proteins in these processes. We go on to discuss the advances, limitations and pitfalls that CK1 researchers encounter when attempting to define rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 149 publications
0
46
0
Order By: Relevance
“…CK1α is one of the seven isoforms (α, β, γ1, γ2, γ3, δ, and ε) of the CK1 serine/threonine kinases family, whose members share homology in the N-terminal kinase domain and similar substrate preferences [ 18 ].…”
Section: General Features Of Ck1α and Ck2: Structure Regulation mentioning
confidence: 99%
See 1 more Smart Citation
“…CK1α is one of the seven isoforms (α, β, γ1, γ2, γ3, δ, and ε) of the CK1 serine/threonine kinases family, whose members share homology in the N-terminal kinase domain and similar substrate preferences [ 18 ].…”
Section: General Features Of Ck1α and Ck2: Structure Regulation mentioning
confidence: 99%
“…Regarding CK1α, the development of selective inhibitors of CK1α is challenging, due to the high degree of homology among CK1 family isoforms [ 18 ]. So far, the pharmacological inactivation with the dual CK1α/CK1δ inhibitor D4476, exerted in cells from MM and other malignancies, produces a cytotoxic effect.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…It is known that the Hippo and Wnt pathways equally regulate the nuclear transcriptional activity and are closely connected to each other on multiple levels [ 74 , 75 , 76 ]. It has been reported that CK1ɛ isoform phosphorylates YAP/TAZ after priming phosphorylation from LATS1/2 and following CK1ɛ binding to MST1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions phosphorylation of DVL is reduced, leading to inhibition of Wnt Signaling. Also, YAP/TAZ complex bind to the cytoplasmic DVL1, preventing phosphorylation and abrogating the complex translocation to the nucleus [ 74 , 75 ]. The A178V DVL1 substitution here described may promote Wnt activation and the expression of target genes by interfering with YAP/TAZ binding sites or preventing the CK1-dependend phosphorylation of DVL1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the participation of RNA helicases in almost all aspects of RNA metabolism increases the safety risks of inhibitors and requires thorough evaluation as multiple vital processes can be interfered with [30]. For example, DDX3 can act as an allosteric activator of casein kinase 1 (CK1) in the Wnt/β-catenin pathway [31], TBK1/IKKε and IFN induction [32], NF-κB signal pathway [33], DNA-damage induced apoptosis [34], etc.…”
Section: Introductionmentioning
confidence: 99%